2019
DOI: 10.7575/aiac.ijels.v.7n.4p.62
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Classroom Management Skills and Self-confidence of Social Studies Teachers

Abstract: This study investigated the relationship between classroom management skills, and self-confidence of social studies teachers. To this end and through a general survey, social studies teachers’ classroom management skills and their self-confidence for education were examined in terms of Gender, Professional Seniority, and Class Size. The population was constituted by 67 social studies teachers working in various secondary schools within the boundaries of the province of Elazig, Turkey, in the spring semester of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…To find out whether the confidence level of teachers differs in classroom assessment about gender, this present study revealed that there is no statistically significant difference between confidence in classroom assessment and the gender of teachers. This finding is consistent with the outcome of a study by Kenan (2019) who revealed that teachers do not differ significantly about their confidence level by gender. This agreed with the current findings which suggested that teachers go through the same form of education and training and hence are all able to perform well in the teaching profession.…”
Section: Discussionsupporting
confidence: 91%
“…To find out whether the confidence level of teachers differs in classroom assessment about gender, this present study revealed that there is no statistically significant difference between confidence in classroom assessment and the gender of teachers. This finding is consistent with the outcome of a study by Kenan (2019) who revealed that teachers do not differ significantly about their confidence level by gender. This agreed with the current findings which suggested that teachers go through the same form of education and training and hence are all able to perform well in the teaching profession.…”
Section: Discussionsupporting
confidence: 91%
“…Several authors agree that classroom management skills represent an effective learning environment (Çakmak, 2019;Marashi & Assgar, 2019;Şanlı, 2019). Through classroom management, teachers tailor the space and conditions in the classroom, monitoring the students' behavior and encouraging them to get involved in the classroom activities (Baş, 2019), as well as negotiating classroom rules with the students (Şanlı, 2019).…”
Section: Practice-based Challengesmentioning
confidence: 99%
“…Additionally, participants mentioned the poor feedback from their teacher mentors regarding their classroom management skills; thus, they remained unsure if they were doing the right thing. Therefore, it is of the utmost importance to recognize that the lack of knowledge about multifaceted aspects of classroom management (Baş, 2019) hinders the teacher's performance. In other words, we believe mentors are responsible for advising preservice teachers during the practicum, clearly indicating the multiple roles they are expected to perform within the classroom so that a lack of awareness in certain classroom matters does not hamper their work.…”
Section: Practice-based Challengesmentioning
confidence: 99%